2004
DOI: 10.1111/j.1399-6576.2004.00387.x
|View full text |Cite
|
Sign up to set email alerts
|

The analgesic effect of morphine on postoperative pain in diabetic patients

Abstract: The findings of the study appear to support experimental and clinical impressions that the analgesic effect of morphine is attenuated in hyperglycemic conditions. Therefore, larger doses of morphine may be administered to diabetic patients for effective postoperative analgesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
30
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 11 publications
6
30
0
Order By: Relevance
“…Previous studies showed that the expression of MOP receptors is down-regulated in the spinal cord of rodents with either nerve injury or type 1 diabetes [54, 55]. These findings may partially explain the reduced analgesic efficacy of opioids in patients with chronic pain and/or neuroinflammatory diseases [7, 9, 56]. Interestingly, emerging evidence shows that pro-inflammatory chemokines such as CCL3-CCR5 signaling is capable of desensitizing MOP receptors, and CCR5 and MOP receptors may engage in crosstalk through dimerization [57, 58].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that the expression of MOP receptors is down-regulated in the spinal cord of rodents with either nerve injury or type 1 diabetes [54, 55]. These findings may partially explain the reduced analgesic efficacy of opioids in patients with chronic pain and/or neuroinflammatory diseases [7, 9, 56]. Interestingly, emerging evidence shows that pro-inflammatory chemokines such as CCL3-CCR5 signaling is capable of desensitizing MOP receptors, and CCR5 and MOP receptors may engage in crosstalk through dimerization [57, 58].…”
Section: Discussionmentioning
confidence: 99%
“…Not only experimental, but also clinical studies have suggested that diabetes or hyperglycemia altered opioid responsiveness. Karci A. et al reported that the analgesic effect of morphine was attenuated in hyperglycemic condition and a large dose of morphine may be administered to diabetic patients for effective postoperative analgesia [13]. Several investigators have studied the endogenous opioid system in type 2 patients that did not respond to stress caused by breathing against fatiguing inspiratory resistive load [14].…”
Section: Introductionmentioning
confidence: 98%
“…Karci et al showed that the analgesic effect of morphine is negatively affected by high blood glucose in patients scheduled for elective total abdominal hysterectomy. According to data on postoperative intravenous patient-controlled analgesia (PCA), patients with diabetes require more opioids than 3 patients without diabetes [4]. Glycated hemoglobin (HbA1c) is a highly reliable indicator of glycemic control over the previous 8 to 12 weeks [5].…”
Section: Introductionmentioning
confidence: 99%
“…The VAS score during activity 24 hours after the operation was higher for the GDM group than for the NGDM group (5[5-6] vs 5 [4][5], P=0.03). No significant between-group differences were found in the pain scores at the 6-hour postoperative rest/activity measurement or at the 24-hour postoperative rest measurement.…”
mentioning
confidence: 95%